Erythritol production by yeasts: a snapshot of current knowledge. Issue 7 (8th February 2018) - Carly, Frédéric; Fickers, Patrick
Abstract: Erythritol is a four‐carbon sugar alcohol produced by microorganisms as an osmoprotectant. It could be used as a natural sweetener in the pharmaceutical and food industries. Here, a snapshot of current knowledge on erythritol metabolism and synthesis, optimization of its production and more precise process and producer strain improvement is presented.